Null Biminimal General Helices in the Lorentzian Heisenberg Group: Essin Turhan, Talat Korpinar - Team, Support (Thai Journal of Mathematics, 2011)
In this paper, we study null biminimal curves in the Lorentzian Heisenberg group Heis3. We characterize non-geodesic null biminimal general helix in terms of its curvatures and torsions in the Lorentzian Heisenberg group Heis3.